2007
DOI: 10.1017/s1121189x00004619
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of the Departments of Mental Health in the Veneto Region ten years after the National Plan 1994-96 for Mental Health. Which implication for clinical practice? Findings from the PICOS Project

Abstract: SUMMARYAims - This study aims to present data on structural and human resources of public mental health services located in the Veneto Region, Italy, and to discuss them in the light of implementation of the first National Target Plan for Mental Health (“Progetto Obiettivo 1994-1996”) ten years after its launch. Methods - The study was conducted in the context of the PICOS (Psychosis Incident Cohort Outcome Study) Project, a large first-presentation multisite study on patients with psychotic disorders attendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
1
10
0
2
Order By: Relevance
“…The burnout prevalence among Italian mental health staff is a cause for concern, as this condition can further deplete public mental health services' already scarce human resources. 29 The proportion of Italian mental health staff scoring above the MBI cut-off was similar to that found by Prosser et al 8 in London (24%), but somewhat lower than reported by other studies conducted in the UK. 36,11 Our results also confirmed the second hypothesis, since burnout has a different impact on the various professional categories, with severe burnout shown to be more frequent among social workers and psychiatrists.…”
Section: Burnout Prevalence Among Mental Health Staffsupporting
confidence: 84%
See 1 more Smart Citation
“…The burnout prevalence among Italian mental health staff is a cause for concern, as this condition can further deplete public mental health services' already scarce human resources. 29 The proportion of Italian mental health staff scoring above the MBI cut-off was similar to that found by Prosser et al 8 in London (24%), but somewhat lower than reported by other studies conducted in the UK. 36,11 Our results also confirmed the second hypothesis, since burnout has a different impact on the various professional categories, with severe burnout shown to be more frequent among social workers and psychiatrists.…”
Section: Burnout Prevalence Among Mental Health Staffsupporting
confidence: 84%
“…All mental health staff employed in the PICOS catchment areas (approximately 3.7 million inhabitants) were eligible for the survey, which examined a wide range of job categories, such as psychiatrists, clinical psychologists, resident psychiatrists, hospital and community psychiatric nurses, occupational therapists, social workers, healthcare support workers, and secretarial staff. 29 The data were collected from January to March 2005. Twenty-two of the 28 collaborating PICOS sites (78.5%) agreed to participate and provided a list of their mental health staff.…”
Section: Participantsmentioning
confidence: 99%
“…Many studies [ 1 - 5 , 7 , 11 - 15 , 18 , 19 ] suggest the importance of job satisfation and work engagement among the workers to prevent burnout and job-related distress and to promote organizational wellbeing. Considerating the findings of the present study, we suppose that high level of perceived job satisfation could be related to the “community centred model” in mental health care services.…”
Section: Discussionmentioning
confidence: 99%
“…The centrality of users and the humanization of care involve many abilieties of the workers, such as listening, continuity in caring, timeliness, good skills in communication, problem solving and crisis management. Furthermore, in Italy as well as in other European countries with a National Public Health System, mental health services are facing severe financial shortages and consequent shortfalls in the number of sector-employed professionals [ 8 - 11 ]. Even more, the quality of the performances depends also on the professional and personal qualities of workers, who often offset structural deficiencies and procedural difficulties with their efforts and highly skilled job.…”
Section: Introductionmentioning
confidence: 99%
“…Family interventions generally consist of non-specific informal support/educational sessions. Specialized individual psychotherapeutic interventions (including CBT) for patients and specialized psychoeducational or cognitive-oriented family interventions are usually not provided because of the lack of trained professionals [26,27]. …”
Section: Methodsmentioning
confidence: 99%